Internal Communication in Improving Employee Performance of Pertamina Bersatu National Cooperative 139 Jakarta - Kusumastuti, Tantri; Furrie, Wulan (PT FORMOSA CENDEKIA GLOBAL, 2024)
KOPNAS PB 139 is a company that has various business units but limited human resources make employees often do work outside the predetermined jobdesk. The ambiguous organizational structure plus the lack of coordination between leaders (chairman) and subordinates (managers) at KOPNAS PB 139 are problems faced by the company. The writing of this research aims to find out, analyze, and evaluate the internal communication aspects applied by KOPNAS PB 139. This research is a qualitative research with a case study method at KOPNAS PB 139. Data collection was conducted through interviews with KOPNAS PB 139 employees. The results showed that internal communication with a horizontal model played an important role in improving employee performance at KOPNAS PB 139 even though vertical internal communication experienced obstacles. There are also still communication barriers such as the accumulation of information and sudden changes in plans from KOPNAS PB 139 clients.